Perancangan Sistem Informasi Pengklasifikasian Rumah Sakit Menggunakan Algoritma K-Means Clustering - Jackri Hendrik; Joni (Bulletin of Computer Science Research, 2024)
Public facilities are facilities provided for public purposes such as roads, street lighting, bus stops, sidewalks, and crossing bridges. The facilities provided are facilities that provide convenience for the community so that they must be properly maintained. Pedestrian facilities function to separate pedestrians from vehicle traffic lanes to ensure pedestrian safety and smooth traffic. Hospitals have a classification according to the Regulation of the Minister of the Republic of Indonesia Number 56 of 2004 concerning Hospital Classification and Licensing. This is in line with research conducted by researchers that not all hospitals treat all problems/diseases that arise in sick individuals, there are classifications that have been stated in these regulations. Text mining is text analysis where data sources are usually obtained from documents, and the goal is to find words that can represent the contents of the document so that an analysis of the  relationships, linkages and classes between documents can be carried out. The Hospital Classification Information System created can classify hospitals based on the data entered which can be accessed using an Android-based smartphone. This Hospital Classification Information System was created using the K-Means Clustering Method in hospital classification.